Bibliometric Analysis of Global Trends in Cardiac Rehabilitation for Patients with Acute Coronary Syndrome - Faisol Faisol; Erna Rochmawati (Indonesian Journal of Global Health Research, 2026)
Cardiac Rehabilitation (CR) is a structured, multidisciplinary program for managing cardiovascular disease that includes education, physical exercise, risk factor modification, and psychosocial support for heart patients, including those who have experienced Acute Coronary Syndrome (ACS).  This study aims to analyze global research trends and examine cardiac rehabilitation from 1964 to 2025. A bibliometric analysis was conducted on publications in the Scopus database, The search strategy:  in this review was based on the following terms: ‘Cardiac Rehabilitation’ and its alternative keywords (‘Acute Coronary syndrome*’, "Cardiac Rehabilitation. These terms were combined using the Boolean operator ‘AND’ to generate a broad range of results. using visualization, co-occurrence, and trend analysis through VOSviewer software (version 1.6.20). The United States made the largest contribution. The most frequently used keywords were "cardiac rehabilitation," "rehabilitation," and "secondary prevention." The most significant publication increases in 2025 (102 publications), 2021 (101 publications), and 2024 (94 publications). The results show fluctuations in research activity, with a significant increase from 2021 to 2025. Further research should focus on developing technology-based rehabilitation models that are accessible from home and affordable, particularly in low-income countries. As telemedicine, which is still seldom discussed and published.